2019
DOI: 10.1016/j.jhepr.2019.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Pcsk9 knockout exacerbates diet-induced non-alcoholic steatohepatitis, fibrosis and liver injury in mice

Abstract: Background & Aims: The fatty acid translocase, also known as CD36, is a well-established scavenger receptor for fatty acid (FA) uptake and is abundantly expressed in many metabolically active tissues. In the liver, CD36 is known to contribute to the progression of non-alcoholic fatty liver disease and to the more severe non-alcoholic steatohepatitis, by promoting triglyceride accumulation and subsequent lipid-induced endoplasmic reticulum (ER) stress. Given the recent discovery that the hepatocyte-secreted pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
57
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 44 publications
10
57
2
Order By: Relevance
“…These experimental findings and clinical observations described in this study indicate that the uncleaved proPCSK9 is an important player in ER stress response. In further support of this conclusion, we have recently demonstrated that Pcsk9 -/mice exhibit increased ER stress, inflammation, insulin resistance and liver injury in response to an ER stress-inducing HFD, compared to Pcsk9 +/+ mice (50). Although individuals harboring mutations in PCSK9 that reduce its abundance in the ER or those treated with PCSK9 gene silencing therapies appear healthy, our data suggest that intracellular PCSK9 may play an important role in maintaining the functionality of the UPR.…”
Section: Discussionmentioning
confidence: 56%
“…These experimental findings and clinical observations described in this study indicate that the uncleaved proPCSK9 is an important player in ER stress response. In further support of this conclusion, we have recently demonstrated that Pcsk9 -/mice exhibit increased ER stress, inflammation, insulin resistance and liver injury in response to an ER stress-inducing HFD, compared to Pcsk9 +/+ mice (50). Although individuals harboring mutations in PCSK9 that reduce its abundance in the ER or those treated with PCSK9 gene silencing therapies appear healthy, our data suggest that intracellular PCSK9 may play an important role in maintaining the functionality of the UPR.…”
Section: Discussionmentioning
confidence: 56%
“…Recent preclinical studies suggest that PCSK9 and LRP1 could modulate NAFLD pathogenesis. PSCK9 deficiency exacerbated the development of hepatic steatosis in HFD-fed mice [ 112 ]. Moreover, hepatic steatosis decreased cell surface LDLR expression and increased plasma ApoB and total cholesterol in a PCSK9-dependent manner [ 110 ].…”
Section: Dyslipidemia: Linking Hepatic Lipid Metabolism and The Heartmentioning
confidence: 99%
“…The reason for not detecting a significant effect in mice fed a chow diet in this study probably relates to the low number of animals used in the chow arm of the experiment related to the main focus on NAFLD. A recent study on C57BL/6J Pcsk9 ‐/‐ mice showed that a high‐fat diet caused severe hepatic steatosis, ER stress inflammation and fibrosis in the livers of Pcsk9 ‐/‐ mice compared to controls 34 . These discrepancies might be related to a different activity of mouse versus human PCSK9, which may be involved in inducing steatosis at intracellular level, and to the diet.…”
Section: Discussionmentioning
confidence: 99%